Diseño de la propuesta de la documentación del sistema de gestión de seguridad y salud en el trabajo SG-SST con base en el Decreto 1072 del 2015 para la empresa Disarchivo Ltda de la ciudad de Bogotá DC (2022)
With the present investigation of the Occupational Health and Safety Management System SG-SST under Decree 1072 of 2015 to the company Disarchivo Ltda., the proposal will be made for planning and carrying out all document management that will comply with the requirements established in the Decree, for its subsequent adaptation and implementation of the SG-SST in the organization, being a necessity the reduction and/or mitigation of risks and dangers during the activities in the different processes of the company, thus ensuring improving the working conditions of employees in terms of safety, care and well-being, resulting in the company and its collaborators having a safe environment being the human resource one of the primary inputs of the productive process.